Enhanced Anti-Tumor Activity of Triptolide in Combination with Irradiation for the Treatment of Oral Cancer - Chen, Yuan-Wu; Lin, Gu-Jiun; Hueng, Dong-Yuan; Huang, Shing-Hwa; Chia, Wei-Tso; Shieh, Yi-Shing; Ma, Kuo-Hsing; Sytwu, Huey-Kang (Planta Medica, 2014)
Advanced oral cancer has a poor prognosis because of the lack of an effective treatment. We explored the efficiency of combined treatment with triptolide and ionizing radiation for treating oral cancer. Human tongue cancer cells were treated with triptolide, ionizing radiation, or triptolide plus ionizing radiation. Cell proliferation, cell cycle arrest, and apoptotic influences were analyzed by FACS and immunohistochemistry. Tumor potency was examined in an in vivo human tongue cancer cells xenograft mouse model. Our results demonstrated that triptolide caused a marked reduction in colony number that was further enhanced with increasing doses of ionizing radiation. Triptolide increased apoptosis and decreased the expression of anti-apoptotic proteins. In vivo, combination treatment synergistically reduced tumor weight and volume possibly via the induction of apoptosis and reduction in anti-apoptotic protein expression. In conclusion, triptolide plus ionizing radiation treatment had synergistic anti-tumor effects, especially in vivo, and may be a promising combined modality therapy for advanced oral cancer.
Keywords: triptolide; ionizing radiation; human tongue cancer cells; Tripterygium wilfordii; Celastraceae